Community Empowerment Through Productive Zakat: Opportunities and Challenges - Mukhlis; M. Syukri Albani Nasution; Isnaini Harahap (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2026)
This study analyzes the effectiveness of community-based productive zakat management implemented by the National Zakat Agency (BAZNAS) in Bengkalis Regency and formulates strategies to optimize its implementation. A qualitative case study approach was employed, with data collected through in-depth interviews, observation, and documentation. The data were analyzed using the Analytical Network Process (ANP), involving 11 expert respondents comprising academics, BAZNAS stakeholders, and zakat practitioners selected through purposive sampling and pairwise comparison. The findings indicate that productive zakat plays a strategic role in community empowerment by providing business capital, enhancing entrepreneurial skills, and strengthening community collaboration. However, its implementation is constrained by incomplete mustahik data, limited literacy and trust among muzakki, and inadequate human resource professionalism. ANP results identify professional, trustworthy, transparent, and collaborative zakat management, supported by enhanced training, mentoring, outreach, and supervision, as the highest strategic priorities. The study suggests that community-based productive zakat has strong potential to serve as a sustainable policy framework for poverty alleviation, reducing social inequality, and supporting the long-term transformation of mustahik into muzakki. Theoretically, this study contributes by integrating empowerment-oriented qualitative findings with ANP-based multi-criteria prioritization, extending Empowerment Theory and the Islamic Social Finance Framework within the context of productive zakat in a coastal-agrarian regency. Practically, the proposed priority model offers BAZNAS Bengkalis and other zakat institutions a decision-support framework for allocating resources, mentoring, and supervision to maximize community empowerment outcomes.